Aspartate metabolic flux promotes nitric oxide to eliminate both antibiotic-sensitive and -resistant Edwardsiella tarda in zebrafish - Xiang, Jiao; Li, Min-yi; Li, Hui (Frontiers in Immunology, 2023)
Metabolic reprogramming potentiates host protection against antibiotic-sensitive or -resistant bacteria.However, it remains unclear whether a single reprogramming metabolite is effective enough to combat both antibiotic-sensitive and -resistant bacteria. This knowledge is key for implementing an antibiotic-free approach. Here, the reprogramming metabolome approach was adopted to characterize the metabolic state of zebrafish infected with tetracycline-sensitive and -resistant Edwardsiella tarda and to identify overlapping depressed aspartate in dying zebrafish as a reprogramming metabolite. Exogenous aspartate protects zebrafish against infection caused by tetracycline-sensitive and -resistant E. tarda. Mechanistically, exogenous aspartate promotes nitric oxide (NO) biosynthesis. NO is a well-documented factor of promoting innate immunity against bacteria, but whether it can play a role in eliminating both tetracycline-sensitive and -resistant E. tarda is unknown. Thus, in this study, aspartate was replaced with sodium nitroprusside to provide NO, which led to similar aspartate-induced protection against tetracycline-sensitive and -resistant E. tarda. These findings support the conclusion that aspartate plays an important protective role through NO against both types of E. tarda. Importantly, we found that tetracycline-sensitive and -resistant E. tarda are sensitive to NO. Therefore, aspartate is an effective reprogramming metabolite that allows implementation of an antibiotic-free approach against bacterial pathogens.